PERENCANAAN DAN SIMULASI SISTEM PNEUMATIK PADA MESIN PRES BRIKET BLOTHONG BERBANTUAN PERANGKAT LUNAK - S.T., M.T., Darto (Jurnal Teknologi dan Manajemen Informatika, 2015)
The use of compressed air is growing over time. Previously, only limited use pressurized air to increase the air pressure in the tires of the vehicle. Currently pneumatic design also has grown considerably so that is no longer done manually but can be done with the help of simulation software , the use of this software is faster and easier in terms of design. The end result of this research is successfully implementing a software simulation of pneumatic systems on blothong briquette press machine